Culinary tourism on the edge of Kali Code: Strategies for the development and empowerment of Kampung Surokarsan - Cininta, Mutiara; Tyas, Hari Saptaning (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The government has constructed a robust embankment in Kampung Surokarsan, formerly a landfill, now providing a clearer view of Kali Code's banks. Nevertheless, residents have not yet tapped into the potential of Kali Code's surroundings for public or tourism purposes. In this densely populated area with predominantly self-employment, the "Code Hijau Asri" farmer group in RT 13 and RT 14, RW 04, strives to enhance welfare and income through urban farming. This study aims to devise strategies for structuring culinary tourism in Surokarsan. Primary data from field observations and interviews complement secondary data from a literature review. SWOT analysis guides strategy formulation, emphasizing Strengths and Opportunities, Weaknesses and Opportunities, Strengths and Threats, Weaknesses and Threats. Tourism strategy follows the 5A approaches: Attractions, Activities, Accessibility, Facilities, and Accommodation, which leverage the urban farmer community and residents skilled in culinary businesses and Brazilian spinach cultivation. The formulated strategy focuses on the legibility of the area's entrance, zoning activities division, and showcasing attractions such as sunset views and urban village ambience.